SOSIALISASI CARA MENGGUNAKAN SOCIAL MEDIA DENGAN BIJAK BAGI IBU-IBU PKK DESA TANJUNG REJO - Anisa Riska; Hasmawati; Awatif; Eko Wulandari; Sukur; Ferinaldi (Hira Institute, 2024)
Digital media is now an important medium used in every society. Digital media has become a modern lifestyle; apart from that, it has helped everyone carry out their routines. Individuals, organizations, and even governments have never been separated from activities using digital media. The method of implementing community service is through three stages: Observation, Discussion, and Counseling. The objectives to be achieved from this activity are to help PKK women in Tanjung Rejo Village use social media and the internet wisely to support the creation of a healthy internet in the community. The benefits of this activity are that Tanjung Rejo Village PKK mothers can be more careful when using the internet, which can be used effectively and efficiently to monitor their children's internet use